Ultra-high-field sodium MRI as biomarker for tumor extent, grade and IDH mutation status in glioma patients - Regnery, Sebastian; Behl, Nicolas G. R.; Platt, Tanja; Weinfurtner, Nina; Windisch, Paul; Deike-Hofmann, Katerina; Sahm, Felix; Bendszus, Martin; Debus, Jürgen; Ladd, Mark E.; Schlemmer, Heinz-Peter; Rieken, Stefan; et al. (NeuroImage: Clinical, 2020)
Purpose - This prospective clinical trial investigated sodium (23Na) MRI at 7 Tesla (T) field strength as biomarker for tumor extent, isocitrate dehydrogenase (IDH) mutation and O6-methylguanine DNA methyltransferase (MGMT) promotor methylation in glioma patients. - Methods - 28 glioma patients underwent 23Na MRI on a 7T scanner (Siemens Healthcare, Erlangen, Germany) parallel to standard 3T MRI before chemoradiation. Areas of Gadolinium-contrast enhancement (gdce), non-enhancing T2-hyperintensity (regarded as edema), necrosis, and normal-appearing white matter (nawm) were segmented on 3T MRI imaging and were co-registered with the 23Na images. The median total 23Na concentrations of all areas were compared by pairwise t-tests. Furthermore, areas of gdce and edema were merged to yield the whole tumor area without necrosis. Subsequently, the difference in median of the 23Na concentration of this whole tumor area was compared between IDH-mutated and IDH wild-type gliomas as well as MGMT methylated and MGMT not-methylated glioblastomas using Whitney-Mann U-tests. All p-values were corrected after the Bonferroni-Holm procedure. - Results - The 23Na concentration increased successively from nawm to necrotic areas (mean ± sd: nawm = 37.84 ± 5.87 mM, edema = 54.69 ± 10.64 mM, gdce = 61.72 ± 12.95 mM, necrosis = 81.88 ± 17.53 mM) and the concentrations differed statistically significantly between all regarded areas (adjusted p-values for all pairwise comparisons < 0.05). Furthermore, IDH-mutated gliomas showed significantly higher 23Na concentrations than IDH wild-type gliomas (median [interquartile range]: IDH wild-type = 52.37 mM [45.98 - 58.56 mM], IDH mutated = 65.02 mM [58.87-67.05 mM], p = 0.039). Among the glioblastomas, there was a trend towards increased 23Na concentration in MGMT methylated tumors that did not reach statistical significance (median [interquartile range]: MGMT methylated = 57.59 mM [50.70 - 59.17 mM], MGMT not methylated = 48.78 mM [45.88 - 53.91 mM], p = 1.0). - Conclusions - 23Na MRI correlates with the IDH mutation status and could therefore enhance image guidance towards biopsy sites as wells as image-guided surgery and radiotherapy. Furthermore, the successive decrease of 23Na concentration from central necrosis to normal-appearing white matter suggests a correlation with tumor infiltration.